Membrane electrode for proton exchange membrane fuel cell and preparation method of membrane electrode
By adopting a multi-layer proton exchange membrane structure and specific catalytic and diffusion layer design, the problems of low mechanical strength, unstable chemical properties and carbon corrosion after the anode reverse are solved in the proton exchange membrane fuel cell, which significantly improves the performance and stability of the fuel cell.
Patent Information
- Application Number
- CN202510135629.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-29
AI Technical Summary
In the existing proton exchange membrane fuel cells, the proton exchange membrane has low mechanical strength and unstable chemical properties, high interface resistance between the catalytic layer and the proton exchange membrane, and carbon corrosion is prone to occur after the anode is reversed.
A multi-layer proton exchange membrane structure is adopted, including an intermediate film layer that is composited with low EW perfluorosulfonic acid resin and PVDF, as well as an alternating layer, a composite inner layer and a composite outer layer arranged alternately. The catalytic layer is a low-EW perfluorosulfonic acid resin mixed with a highly graphitized carbon-based platinum carbon catalyst, and the diffusion layer includes a low-graphitized carbon layer and a medium-graphitized carbon fiber layer, both of which have been hydrophobic.
It significantly improves the mechanical strength and chemical stability of the proton exchange membrane, reduces the interface resistance between the catalytic layer and the proton exchange membrane, effectively prevents carbon corrosion after the anode reverse, and improves the performance and stability of the fuel cell.
Smart Images

Figure CN119905601A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of proton exchange membrane fuel cells, and in particular relates to a membrane electrode for a proton exchange membrane fuel cell and a preparation method thereof. Background Art
[0002] As the core material of fuel cell membrane electrode, the performance of proton exchange membrane directly affects the performance and service life of fuel cells. An ideal proton exchange membrane should have the characteristics of high proton conductivity, low electronic conductivity, low gas permeability, good chemical, electrochemical and thermal stability. At present, in order to solve the problems of low mechanical strength and unstable chemical properties of existing membrane electrode proton exchange membranes, the existing technology mainly changes the degree of polymerization of membrane materials and the ratio between long chains and short chains to improve the stability of the material, but the corresponding material preparation process of this method is relatively complex and uncontrollable.
[0003] The problem of high interface resistance between the catalyst layer and the proton exchange membrane of proton exchange membrane fuel cells is currently mainly solved by direct catalyst coating technology, which increases the contact area between the catalyst and the proton exchange membrane by directly coating the catalyst on both sides of the proton exchange membrane. However, this technology has high requirements for slurry ratio, coating process and equipment, resulting in high costs.
[0004] Regarding the problem of carbon corrosion after anode reverse polarity, when there is not enough fuel in the local anode of the stack to provide current, reverse polarity will occur. In order to reduce or prevent carbon corrosion reactions, the current solution is to develop alternative reactions that can occur before carbon corrosion, such as water electrolysis reactions. The conventional method is to add an OER (oxygen evolution reaction) catalyst to the anode catalyst layer to enhance the anode's ability to resist reverse polarity. However, the catalyst is generally a precious metal such as iridium, which greatly increases the cost of the membrane electrode. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a membrane electrode for a proton exchange membrane fuel cell and a preparation method thereof in view of the above-mentioned deficiencies in the prior art, which can effectively improve the mechanical strength and chemical stability of the proton exchange membrane, and at the same time solve the carbon corrosion caused by anode reversal.
[0006] The technical solution adopted by the present invention is: a membrane electrode for a proton exchange membrane fuel cell, comprising a multi-layer proton exchange membrane and a catalyst layer and a diffusion layer symmetrically arranged on both sides of the multi-layer proton exchange membrane from the inside to the outside;
[0007] The multilayer proton exchange membrane comprises an intermediate membrane layer formed by a composite of a low-EW perfluorosulfonic acid resin and PVDF, and alternating layers, a composite inner layer and a composite outer layer symmetrically arranged on both sides of the intermediate membrane layer from the inside to the outside;
[0008] The alternating layers are alternately composed of at least two low EW perfluorosulfonic acid resin film layers and at least two high EW perfluorosulfonic acid resin film layers;
[0009] The composite inner layer is a mixture of low EW perfluorosulfonic acid resin and rare metal oxides and dopants thereof;
[0010] The composite outer layer is a mixture of low EW perfluorosulfonic acid resin and nano-platinum metal;
[0011] The catalytic layer is a mixture of a low-EW perfluorosulfonic acid resin and a highly graphitized carbon-based platinum-carbon catalyst;
[0012] The diffusion layer comprises a low-graphitized carbon layer and a medium-graphitized carbon fiber layer arranged from the inside to the outside, and the low-graphitized carbon layer and the medium-graphitized carbon fiber layer are both treated with hydrophobicity.
[0013] Preferably, the ion exchange equivalent of the low EW perfluorosulfonic acid resin and the low EW fluorosulfonic acid resin membrane layer is 600 g / mol-1000 g / mol, and lower than 1000 g / mol; the ion exchange equivalent of the high EW perfluorosulfonic acid resin and the high EW fluorosulfonic acid resin membrane layer is 1000 g / mol-1200 g / mol.
[0014] Preferably, the rare metal oxides and dopants thereof in the composite inner layer include CeO2, Ce 0.8 G 0.2 O 1.9 ,BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ 、BaZr 0.8 Yb 0.2 O 3-σ One or more of .
[0015] Preferably, the high-graphitization carbon-based platinum-carbon catalyst adopts a carbon-based treatment temperature of 2000°C-3000°C to achieve a high degree of graphitization; the medium-graphitization carbon fiber layer adopts a carbon treatment temperature of 1800°C-2000°C, and below 2000°C to achieve a medium degree of graphitization; the low-graphitization carbon layer adopts a carbon treatment temperature of 1400°C-1800°C, and below 1800°C to achieve a low degree of graphitization.
[0016] Preferably, the thickness of the intermediate membrane layer is 3-5 μm; the thickness of the low EW perfluorosulfonic acid resin membrane layer is 1-2 μm; the thickness of the high EW perfluorosulfonic acid resin membrane layer is 1-2 μm; the thickness of the composite inner layer is 1-2 μm; the thickness of the composite outer layer is 1-2 μm; the thickness of the multilayer proton exchange membrane is 10-30 μm; the thickness of the catalytic layer is 10-15 μm; the thickness of the low graphitized carbon layer in the diffusion layer is 10-15 μm, and the thickness of the medium graphitized carbon fiber layer is 150-500 μm.
[0017] A method for preparing a membrane electrode for a proton exchange membrane fuel cell comprises the following steps:
[0018] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and a high dielectric small molecule alcohol with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and the high dielectric small molecule alcohol in a volume ratio of 20%-30%: 5%-10%: 60%-75% to obtain a low EW perfluorosulfonic acid resin composite 5%-10% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0019] S2: preparing an alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol and directly stirring and mixing it with a high dielectric small molecule alcohol to obtain a low EW perfluorosulfonic acid resin slurry with a solid content of 20%-30%; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1000g / mol-1200g / mol and directly stirring and mixing it with a high dielectric small molecule alcohol to obtain a high EW perfluorosulfonic acid resin slurry with a solid content of 20%-30%;
[0020] S3: preparing a composite inner layer slurry, selecting a perfluorosulfonic acid resin, a rare metal oxide and a dopant thereof, and a high dielectric small molecule alcohol with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, the rare metal oxide and a dopant thereof, and the high dielectric small molecule alcohol in a volume ratio of 20%-30%: 5%-10%: 60%-75% to obtain a low EW perfluorosulfonic acid resin slurry containing a rare metal oxide and a dopant thereof, i.e., a composite inner layer slurry;
[0021] S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin, nano-platinum metal and a high dielectric small molecule alcohol with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, nano-platinum metal and high dielectric small molecule alcohol in a volume ratio of 20%-30%: 5%-10%: 60%-75% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry;
[0022] S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol, using a highly graphitized carbon-based platinum-carbon catalyst and a high dielectric small molecule alcohol obtained by a carbon-based treatment temperature of 2000°C-3000°C, and directly stirring and mixing the perfluorosulfonic acid resin, the highly graphitized carbon-based platinum-carbon catalyst and the high dielectric small molecule alcohol in a volume ratio of 2%-5%: 0.8%-4%: 91%-97.2% to obtain a catalytic layer slurry;
[0023] S6: preparing a diffusion layer, using a carbon treatment temperature of 1800°C-2000°C but lower than 2000°C to obtain a medium-graphitized carbon fiber layer, and performing a hydrophobic treatment on the medium-graphitized carbon fiber layer; and then using a carbon treatment temperature of 1400°C-1800°C but lower than 1800°C to obtain a low-graphitized carbon layer;
[0024] S7: preparing a multilayer proton exchange membrane, preparing an intermediate membrane layer by using an intermediate membrane layer slurry, and after drying, alternately preparing at least two layers of low-EW perfluorosulfonic acid resin membrane layers and high-EW perfluorosulfonic acid resin membrane layers on the surface of the intermediate membrane layer by using a low-EW perfluorosulfonic acid resin slurry and a high-EW perfluorosulfonic acid resin slurry, drying after each preparation, preparing a composite inner layer by using a composite inner layer slurry on the surface of the top high-EW perfluorosulfonic acid resin membrane layer, and preparing a composite outer layer by using a composite outer layer slurry on the surface of the composite inner layer after drying, and after drying, turning the intermediate membrane layer over and repeating the above steps, symmetrically preparing membrane layers with the same structure to obtain a multilayer proton exchange membrane;
[0025] S8: Prepare a membrane electrode for a proton exchange membrane fuel cell, prepare a catalytic layer on both sides of the multilayer proton exchange membrane using a catalytic layer slurry, apply a perfluorosulfonic acid resin solution on the edge of the catalytic layer surface after drying, and bond the low-graphitization carbon layer and the medium-graphitization carbon fiber layer prepared in S6 to obtain a membrane electrode for a proton exchange membrane fuel cell after bonding.
[0026] Preferably, the rare metal oxide and its dopant in step S3 include CeO2, Ce 0.8 G 0.2 O 1.9 ,BaCe 0.7 Zr0 .1Y 0.1 Yb 0.1 O 3-σ 、BaZr 0.8 Yb 0.2 O 3-σ One or more of the following: rare metal oxides and their dopants can act as free radical scavengers (FRS), which preferentially react with free radicals to protect the proton exchange membrane from chemical degradation. They have the advantages of preferentially reacting with free radicals, being able to regenerate to ensure long-term effectiveness, and being insoluble in acidic aqueous media to prevent loss in water. Moreover, FRS is directly added during the preparation of the proton exchange membrane without the need for additional steps, and the process is simple.
[0027] Preferably, the high dielectric small molecule alcohol includes one or more of ethanol, ethylene glycol, n-propanol, and isopropanol.
[0028] Preferably, the intermediate film layer, the low EW perfluorosulfonic acid resin film layer, the high EW perfluorosulfonic acid resin film layer, the composite inner layer, the composite outer layer and the catalytic layer are all prepared by coating or screen printing.
[0029] The beneficial effects of the present invention are:
[0030] (1) The middle membrane layer uses low EW perfluorosulfonic acid resin with PVDF added, which can effectively improve the mechanical strength of the proton exchange membrane and improve its durability during repeated swelling;
[0031] (2) Low EW perfluorosulfonic acid resin can improve electrical conductivity, and high EW perfluorosulfonic acid resin has higher strength. Alternating and overlapping low EW perfluorosulfonic acid resin membrane layers and high EW perfluorosulfonic acid resin membrane layers is beneficial to mass transfer in high-density electrical regions, thereby significantly improving the performance of fuel cells while ensuring mechanical strength;
[0032] (3) By preparing a composite inner layer containing rare metal oxides and their impurities and a composite outer layer containing nano-platinum metal, it is beneficial to eliminate the corrosion of the proton exchange membrane by free radicals;
[0033] (4) By setting different graphitization degrees of the highly graphitized catalyst layer, the medium graphitized carbon fiber layer and the low graphitized carbon layer, when the anode is reversed, the medium graphitized carbon fiber layer and the low graphitized carbon layer with low graphitization degree can be sacrificed, thereby preserving the structure and activity of the highly graphitized catalyst layer and the proton exchange membrane, thereby effectively improving the stability of the fuel cell.
[0034] The membrane electrode for proton exchange membrane fuel cells prepared by the present invention has the characteristics of high mechanical strength and stable chemical properties, and also effectively solves the problems of high interface resistance between the catalyst layer and the proton exchange membrane of the proton exchange membrane fuel cell and carbon corrosion after anode reversal. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of the layered structure of the present invention;
[0036] Figure 2 The power spectra of Examples 1-5 and Comparative Examples 1-2 that vary with time are shown;
[0037] Figure 3 This is the carbon corrosion test spectrum after anode reversal in Example 5 of the present invention;
[0038] Figure 4 This is the carbon corrosion test spectrum after anode reversal in comparative example 3 of the present invention.
[0039] In the figure: 1. middle membrane layer; 2. low EW perfluorosulfonic acid resin membrane layer; 3. high EW perfluorosulfonic acid resin membrane layer; 4. composite inner layer; 5. composite outer layer; 6. catalytic layer; 7. low graphitized carbon layer; 8. medium graphitized carbon fiber layer. DETAILED DESCRIPTION
[0040] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0041] Example 1
[0042] like Figure 1 As shown, the membrane electrode for proton exchange membrane fuel cell provided in this embodiment is manufactured by the following steps:
[0043] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and n-propanol with an ion exchange equivalent of 900 g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and n-propanol in a volume ratio of 20%:5%:75% to obtain a low EW perfluorosulfonic acid resin composite 5% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0044] S2: preparing alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol and isopropanol, and directly stirring and mixing them, with a solid content of 20%, to obtain a low EW perfluorosulfonic acid resin slurry; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1200 g / mol and isopropanol, and directly stirring and mixing them, with a solid content of 20%, to obtain a high EW perfluorosulfonic acid resin slurry;
[0045] S3: Prepare the composite inner layer slurry, select perfluorosulfonic acid resin with an ion exchange equivalent of 900g / mol, Ce 0.8 G 0.2 O 1.9 and ethanol, the perfluorosulfonic acid resin, Ce 0.8 G 0.2 O 1.9and ethanol in a volume ratio of 20%:5%:75% and stirred to obtain Ce-containing 0.8 G 0.2 O 1.9 Low EW perfluorosulfonic acid resin slurry, i.e. composite inner layer slurry;
[0046] S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol, a nano-platinum metal with a particle size of 20 nm-50 nm, and isopropanol, and directly stirring and mixing the perfluorosulfonic acid resin, the nano-platinum metal, and the isopropanol in a volume ratio of 20%:5%:75% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry;
[0047] S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol, a highly graphitized carbon-based platinum-carbon catalyst obtained at a carbon-based treatment temperature of 2000° C., and isopropanol; firstly wetting the highly graphitized carbon-based platinum-carbon catalyst, and then directly stirring and mixing the wetted highly graphitized carbon-based platinum-carbon catalyst, the perfluorosulfonic acid resin, and the isopropanol in a volume ratio of 0.8%:2%:97.2% to obtain a catalytic layer slurry;
[0048] S6: preparing a diffusion layer, using a carbon treatment temperature of 1800° C. to obtain a medium graphitized carbon fiber layer 8, and performing a hydrophobic treatment on the medium graphitized carbon fiber layer 8; then using a carbon treatment temperature of 1400° C. to obtain a low graphitized carbon layer 7, and performing a hydrophobic treatment on the low graphitized carbon layer 7;
[0049] S7: Prepare a multilayer proton exchange membrane by screen printing the intermediate membrane slurry prepared in step S1 into a 6*6 cm 2 The low EW perfluorosulfonic acid resin is compounded with a 5% PVDF film layer, and the film layer thickness is 5 μm, that is, a 5 μm intermediate film layer 1 is prepared;
[0050] After the intermediate film layer 1 is dried, the low EW perfluorosulfonic acid resin slurry prepared in step S2 is first coated on one side of the intermediate film layer 1, that is, a low EW perfluorosulfonic acid resin film layer 2 is obtained by coating, and the film layer thickness is 2 μm. After drying, the high EW perfluorosulfonic acid resin slurry prepared in step S2 is then coated, that is, a high EW perfluorosulfonic acid resin film layer 3 is obtained by coating, and the film layer thickness is 2 μm. Then, a layer of low EW perfluorosulfonic acid resin film layer 2 with a thickness of 2 μm and a layer of high EW perfluorosulfonic acid resin film layer 3 with a thickness of 2 μm are sequentially coated, and the preparation of the alternating layers is completed;
[0051] The surface of the high EW perfluorosulfonic acid resin film layer 3 is coated with the Ce-containing 0.8 G 0.2 O 1.9The low EW perfluorosulfonic acid resin slurry is coated to obtain a composite inner layer 4, and the film thickness is 2 μm;
[0052] The low EW perfluorosulfonic acid resin slurry containing nano-platinum metal prepared in step S4 is coated on the surface of the composite inner layer 4, that is, the composite outer layer 5 is obtained by coating, and the film thickness is 2 μm;
[0053] After the composite inner layer 4 is dried, the composite membrane layer is turned over, and the above coating steps are repeated on the other side of the intermediate membrane layer 1, and the membrane layers with the same structure are symmetrically coated with the intermediate membrane layer 1 as the center, thus completing the preparation of the multilayer proton exchange membrane;
[0054] S8: preparing a membrane electrode for a proton exchange membrane fuel cell, symmetrically coating the catalyst layer slurry prepared in S5 on both sides of the multilayer proton exchange membrane, thereby coating the two side surfaces of the multilayer proton exchange membrane to obtain a catalyst layer 6, the thickness of the catalyst layer 6 on each side is 10 μm, and a functional structure is formed after the coating is completed;
[0055] The edges of both sides of the functional structure are dotted with a 5% solid content perfluorosulfonic acid resin solution, and the 5.5*5.5 cm 2 The low graphitized carbon layer 7 and the medium graphitized carbon fiber layer 8 are formed, the thickness of the low graphitized carbon layer 7 is 10 μm, and the thickness of the medium graphitized carbon fiber layer 8 is 500 μm, thus completing the bonding of the diffusion layer. After the diffusion layer is bonded, the membrane electrode for the proton exchange membrane fuel cell is obtained.
[0056] Example 2
[0057] The membrane electrode for the proton exchange membrane fuel cell provided in this embodiment is manufactured by the following steps:
[0058] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and isopropanol with an ion exchange equivalent of 600 g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and isopropanol in a volume ratio of 30%:10%:60% to obtain a low EW perfluorosulfonic acid resin composite 10% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0059] S2: preparing alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 30%, to obtain a low EW perfluorosulfonic acid resin slurry; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1200 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 30%, to obtain a high EW perfluorosulfonic acid resin slurry;
[0060] S3: Prepare the composite inner layer slurry, select perfluorosulfonic acid resin with an ion exchange equivalent of 600g / mol, BaZr 0.8 Yb 0.2 O3-σ and ethylene glycol, perfluorosulfonic acid resin, BaZr 0.8 Yb 0.2 O 3-σ and ethylene glycol in a volume ratio of 30%:10%:60% and stirred to obtain a mixture containing BaZr 0.8 Yb 0.2 O 3-σ Low EW perfluorosulfonic acid resin slurry, i.e. composite inner layer slurry;
[0061] S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a nano-platinum metal with a particle size of 20 nm-50 nm, and ethanol, and directly stirring and mixing the perfluorosulfonic acid resin, the nano-platinum metal, and the ethanol in a volume ratio of 30%:10%:60% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry;
[0062] S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a highly graphitized carbon-based platinum-carbon catalyst obtained by a carbon-based treatment temperature of 2600° C., and isopropanol; firstly wetting the highly graphitized carbon-based platinum-carbon catalyst, and then directly stirring and mixing the wetted highly graphitized carbon-based platinum-carbon catalyst, the perfluorosulfonic acid resin, and the isopropanol in a volume ratio of 4%:5%:91% to obtain a catalytic layer slurry;
[0063] S6: preparing a diffusion layer, using a carbon treatment temperature of 1950° C. to obtain a medium graphitized carbon fiber layer 8, and performing a hydrophobic treatment on the medium graphitized carbon fiber layer 8; then using a carbon treatment temperature of 1700° C. to obtain a low graphitized carbon layer 7, and performing a hydrophobic treatment on the low graphitized carbon layer 7;
[0064] S7: Prepare a multilayer proton exchange membrane by coating the intermediate membrane slurry prepared in step S1 into a 6*6 cm 2 The low EW perfluorosulfonic acid resin is compounded with a 10% PVDF film layer, and the film layer thickness is 3 μm, that is, a 3 μm intermediate film layer 1 is prepared;
[0065] After the intermediate film layer 1 is dried, the low EW perfluorosulfonic acid resin slurry prepared in step S2 is first coated on one side of the intermediate film layer 1, that is, a low EW perfluorosulfonic acid resin film layer 2 is obtained by coating, and the film layer thickness is 2 μm. After drying, the high EW perfluorosulfonic acid resin slurry prepared in step S2 is then coated, that is, a high EW perfluorosulfonic acid resin film layer 3 is obtained by coating, and the film layer thickness is 2 μm. Then, a layer of low EW perfluorosulfonic acid resin film layer 2 with a thickness of 2 μm and a layer of high EW perfluorosulfonic acid resin film layer 3 with a thickness of 2 μm are sequentially coated, and the preparation of the alternating layers is completed;
[0066] The surface of the high EW perfluorosulfonic acid resin film layer 3 is coated with the BaZr-containing0.8 Yb 0.2 O 3-σ The low EW perfluorosulfonic acid resin slurry is coated to obtain a composite inner layer 4, and the film thickness is 1 μm;
[0067] The low EW perfluorosulfonic acid resin slurry containing nano-platinum metal prepared in step S4 is coated on the surface of the composite inner layer 4, that is, the composite outer layer 5 is obtained by coating, and the film thickness is 1 μm;
[0068] After the composite inner layer 4 is dried, the composite membrane layer is turned over, and the above coating steps are repeated on the other side of the intermediate membrane layer 1, and the membrane layers with the same structure are symmetrically coated with the intermediate membrane layer 1 as the center, thus completing the preparation of the multilayer proton exchange membrane;
[0069] S8: preparing a membrane electrode for a proton exchange membrane fuel cell, symmetrically coating the catalyst layer slurry prepared in S5 on both sides of the multilayer proton exchange membrane, thereby coating the two side surfaces of the multilayer proton exchange membrane to obtain a catalyst layer 6, the thickness of the catalyst layer 6 on each side is 10 μm, and a functional structure is formed after the coating is completed;
[0070] The edges of both sides of the functional structure are dotted with a 15% solid content perfluorosulfonic acid resin solution, and the 5.5*5.5 cm 2 The low graphitized carbon layer 7 and the medium graphitized carbon fiber layer 8 are formed, the thickness of the low graphitized carbon layer 7 is 15 μm, and the thickness of the medium graphitized carbon fiber layer 8 is 150 μm, thus completing the bonding of the diffusion layer. After the diffusion layer is bonded, the membrane electrode for the proton exchange membrane fuel cell is obtained.
[0071] Example 3
[0072] The membrane electrode for the proton exchange membrane fuel cell provided in this embodiment is manufactured by the following steps:
[0073] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and isopropanol with an ion exchange equivalent of 900 g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and isopropanol in a volume ratio of 30%:10%:60% to obtain a low EW perfluorosulfonic acid resin composite 10% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0074] S2: preparing alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 30%, to obtain a low EW perfluorosulfonic acid resin slurry; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1200 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 30%, to obtain a high EW perfluorosulfonic acid resin slurry;
[0075] S3: Prepare the composite inner layer slurry, select perfluorosulfonic acid resin with an ion exchange equivalent of 900g / mol, CeO2 and Ce with a mass ratio of 1:1 0.8 G 0.2 O 1.9 mixture and ethylene glycol, perfluorosulfonic acid resin, CeO2 and Ce 0.8 G 0.2 O 1.9 The mixture and ethylene glycol were directly stirred and mixed in a volume ratio of 30%:10%:60% to obtain a mixture containing CeO2 and Ce 0.8 G 0.2 O 1.9 Low EW perfluorosulfonic acid resin slurry, i.e. composite inner layer slurry;
[0076] S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol, a nano-platinum metal with a particle size of 20 nm-50 nm, and ethanol, and directly stirring and mixing the perfluorosulfonic acid resin, the nano-platinum metal, and the ethanol in a volume ratio of 30%:10%:60% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry;
[0077] S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol, a highly graphitized carbon-based platinum-carbon catalyst obtained at a carbon-based treatment temperature of 2200° C., and isopropanol; firstly wetting the highly graphitized carbon-based platinum-carbon catalyst, and then directly stirring and mixing the wetted highly graphitized carbon-based platinum-carbon catalyst, the perfluorosulfonic acid resin, and the isopropanol in a volume ratio of 4%:5%:91% to obtain a catalytic layer slurry;
[0078] S6: preparing a diffusion layer, using a carbon treatment temperature of 1850° C. to obtain a medium graphitized carbon fiber layer 8, and performing a hydrophobic treatment on the medium graphitized carbon fiber layer 8; then using a carbon treatment temperature of 1500° C. to obtain a low graphitized carbon layer 7, and performing a hydrophobic treatment on the low graphitized carbon layer 7;
[0079] S7: Prepare a multilayer proton exchange membrane by screen printing the intermediate membrane slurry prepared in step S1 into a 6*6 cm 2 The low EW perfluorosulfonic acid resin is compounded with a 10% PVDF film layer, and the film layer thickness is 3 μm, that is, a 3 μm intermediate film layer 1 is prepared;
[0080] After the intermediate film layer 1 is dried, the low EW perfluorosulfonic acid resin slurry prepared in step S2 is first coated on one side of the intermediate film layer 1, that is, a low EW perfluorosulfonic acid resin film layer 2 is obtained by coating, and the film layer thickness is 1 μm. After drying, the high EW perfluorosulfonic acid resin slurry prepared in step S2 is then coated, that is, a high EW perfluorosulfonic acid resin film layer 3 is obtained by coating, and the film layer thickness is 2 μm. Then, a layer of low EW perfluorosulfonic acid resin film layer 2 with a thickness of 1 μm and a layer of high EW perfluorosulfonic acid resin film layer 3 with a thickness of 2 μm are sequentially coated, and the preparation of the alternating layers is completed;
[0081] The surface of the high EW perfluorosulfonic acid resin film layer 3 is coated with the CeO2 and Ce prepared in step S3. 0.8 G 0.2 O 1.9 The low EW perfluorosulfonic acid resin slurry is coated to obtain a composite inner layer 4, and the film thickness is 1 μm;
[0082] The low EW perfluorosulfonic acid resin slurry containing nano-platinum metal prepared in step S4 is coated on the surface of the composite inner layer 4, that is, the composite outer layer 5 is obtained by coating, and the film thickness is 1 μm;
[0083] After the composite inner layer 4 is dried, the composite membrane layer is turned over, and the above coating steps are repeated on the other side of the intermediate membrane layer 1, and the membrane layers with the same structure are symmetrically coated with the intermediate membrane layer 1 as the center, thus completing the preparation of the multilayer proton exchange membrane;
[0084] S8: preparing a membrane electrode for a proton exchange membrane fuel cell, symmetrically coating the catalyst layer slurry prepared in S5 on both sides of the multilayer proton exchange membrane, thereby coating the two side surfaces of the multilayer proton exchange membrane to obtain a catalyst layer 6, the thickness of the catalyst layer 6 on each side is 10 μm, and a functional structure is formed after the coating is completed;
[0085] The edges of both sides of the functional structure are dotted with a 5% solid content perfluorosulfonic acid resin solution, and the 5.5*5.5 cm 2 The low graphitized carbon layer 7 and the medium graphitized carbon fiber layer 8 are formed, the thickness of the low graphitized carbon layer 7 is 10 μm, and the thickness of the medium graphitized carbon fiber layer 8 is 200 μm, thus completing the bonding of the diffusion layer. After the diffusion layer is bonded, the membrane electrode for the proton exchange membrane fuel cell is obtained.
[0086] Example 4
[0087] The membrane electrode for the proton exchange membrane fuel cell provided in this embodiment is manufactured by the following steps:
[0088] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and isopropanol with an ion exchange equivalent of 900 g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and n-propanol in a volume ratio of 25%:8%:65% to obtain a low EW perfluorosulfonic acid resin composite 8% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0089] S2: preparing alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 25%, to obtain a low EW perfluorosulfonic acid resin slurry; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1100 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 25%, to obtain a high EW perfluorosulfonic acid resin slurry;
[0090] S3: Prepare the composite inner layer slurry, select perfluorosulfonic acid resin with an ion exchange equivalent of 900g / mol, BaZr 0.8 Yb 0.2 O 3-σ and ethylene glycol, perfluorosulfonic acid resin, BaZr 0.8 Yb 0.2 O 3-σ and ethylene glycol in a volume ratio of 25%:5%:70% and stirred to obtain a mixture containing BaZr 0.8 Yb 0.2 O 3-σ Low EW perfluorosulfonic acid resin slurry, i.e. composite inner layer slurry;
[0091] S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol, a nano-platinum metal with a particle size of 20 nm-50 nm, and ethanol, and directly stirring and mixing the perfluorosulfonic acid resin, the nano-platinum metal, and the ethanol in a volume ratio of 30%:10%:60% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry;
[0092] S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 900 g / mol, a highly graphitized carbon-based platinum-carbon catalyst obtained at a carbon-based treatment temperature of 2400° C., and isopropanol; firstly wetting the highly graphitized carbon-based platinum-carbon catalyst, and then directly stirring and mixing the wetted highly graphitized carbon-based platinum-carbon catalyst, the perfluorosulfonic acid resin, and the isopropanol in a volume ratio of 2%:7%:91% to obtain a catalytic layer slurry;
[0093] S6: preparing a diffusion layer, using a carbon treatment temperature of 1900° C. to obtain a medium graphitized carbon fiber layer 8, and performing a hydrophobic treatment on the medium graphitized carbon fiber layer 8; then using a carbon treatment temperature of 1600° C. to obtain a low graphitized carbon layer 7, and performing a hydrophobic treatment on the low graphitized carbon layer 7;
[0094] S7: Prepare a multilayer proton exchange membrane by screen printing the intermediate membrane slurry prepared in step S1 into a 6*6 cm 2 The low EW perfluorosulfonic acid resin is compounded with an 8% PVDF film layer, and the film layer thickness is 5 μm, that is, a 5 μm intermediate film layer 1 is prepared;
[0095] After the intermediate film layer 1 is dried, the low EW perfluorosulfonic acid resin slurry prepared in step S2 is first coated on one side of the intermediate film layer 1, that is, a low EW perfluorosulfonic acid resin film layer 2 is obtained by coating, and the film layer thickness is 2 μm. After drying, the high EW perfluorosulfonic acid resin slurry prepared in step S2 is then coated, that is, a high EW perfluorosulfonic acid resin film layer 3 is obtained by coating, and the film layer thickness is 1 μm. Then, a layer of low EW perfluorosulfonic acid resin film layer 2 with a thickness of 2 μm and a layer of high EW perfluorosulfonic acid resin film layer 3 with a thickness of 1 μm are sequentially coated, and the preparation of the alternating layers is completed;
[0096] The surface of the high EW perfluorosulfonic acid resin film layer 3 is coated with the BaZr-containing 0.8 Yb 0.2 O 3-σ The low EW perfluorosulfonic acid resin slurry is coated to obtain a composite inner layer 4, and the film thickness is 1 μm;
[0097] The low EW perfluorosulfonic acid resin slurry containing nano-platinum metal prepared in step S4 is coated on the surface of the composite inner layer 4, that is, the composite outer layer 5 is obtained by coating, and the film thickness is 1 μm;
[0098] After the composite inner layer 4 is dried, the composite membrane layer is turned over, and the above coating steps are repeated on the other side of the intermediate membrane layer 1, and the membrane layers with the same structure are symmetrically coated with the intermediate membrane layer 1 as the center, thus completing the preparation of the multilayer proton exchange membrane;
[0099] S8: preparing a membrane electrode for a proton exchange membrane fuel cell, symmetrically coating the catalyst layer slurry prepared in S5 on both sides of the multilayer proton exchange membrane, thereby coating the two side surfaces of the multilayer proton exchange membrane to obtain a catalyst layer 6, the thickness of the catalyst layer 6 on each side is 15 μm, and a functional structure is formed after the coating is completed;
[0100] The edges of both sides of the functional structure are dotted with a 15% solid content perfluorosulfonic acid resin solution, and the 5.5*5.5 cm 2 The low graphitized carbon layer 7 and the medium graphitized carbon fiber layer 8 are formed, the thickness of the low graphitized carbon layer 7 is 15 μm, and the thickness of the medium graphitized carbon fiber layer 8 is 400 μm, thus completing the bonding of the diffusion layer. After the diffusion layer is bonded, the membrane electrode for the proton exchange membrane fuel cell is obtained.
[0101] Example 5
[0102] The membrane electrode for the proton exchange membrane fuel cell provided in this embodiment is manufactured by the following steps:
[0103] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and isopropanol with an ion exchange equivalent of 600 g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and isopropanol in a volume ratio of 25%:5%:70% to obtain a low EW perfluorosulfonic acid resin composite 5% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0104] S2: preparing alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 25%, to obtain a low EW perfluorosulfonic acid resin slurry; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1000 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 25%, to obtain a high EW perfluorosulfonic acid resin slurry;
[0105] S3: Prepare the composite inner layer slurry, select perfluorosulfonic acid resin with an ion exchange equivalent of 600g / mol, BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ and ethylene glycol, perfluorosulfonic acid resin, BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ and ethylene glycol in a volume ratio of 25%:5%:70% and stirred to obtain a mixture containing BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ Low EW perfluorosulfonic acid resin slurry, i.e. composite inner layer slurry;
[0106] S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a nano-platinum metal with a particle size of 20 nm-50 nm, and ethanol, and directly stirring and mixing the perfluorosulfonic acid resin, the nano-platinum metal, and the ethanol in a volume ratio of 33%:2%:65% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry;
[0107] S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a highly graphitized carbon-based platinum-carbon catalyst obtained at a carbon-based treatment temperature of 2800° C., and isopropanol; firstly wetting the highly graphitized carbon-based platinum-carbon catalyst, and then directly stirring and mixing the wetted highly graphitized carbon-based platinum-carbon catalyst, the perfluorosulfonic acid resin, and the isopropanol in a volume ratio of 2%:7%:91% to obtain a catalytic layer slurry;
[0108] S6: preparing a diffusion layer, using a carbon treatment temperature of 1980° C. to obtain a medium graphitized carbon fiber layer 8, and performing a hydrophobic treatment on the medium graphitized carbon fiber layer 8; then using a carbon treatment temperature of 1750° C. to obtain a low graphitized carbon layer 7, and performing a hydrophobic treatment on the low graphitized carbon layer 7;
[0109] S7: Prepare a multilayer proton exchange membrane by screen printing the intermediate membrane slurry prepared in step S1 into a 6*6 cm 2 The low EW perfluorosulfonic acid resin is compounded with a 5% PVDF film layer, and the film layer thickness is 4 μm, that is, a 4 μm intermediate film layer 1 is prepared;
[0110] After the intermediate film layer 1 is dried, the low EW perfluorosulfonic acid resin slurry prepared in step S2 is first coated on one side of the intermediate film layer 1, that is, a low EW perfluorosulfonic acid resin film layer 2 is obtained by coating, and the film layer thickness is 1 μm. After drying, the high EW perfluorosulfonic acid resin slurry prepared in step S2 is then coated, that is, a high EW perfluorosulfonic acid resin film layer 3 is obtained by coating, and the film layer thickness is 1 μm. Then, a layer of low EW perfluorosulfonic acid resin film layer 2 with a thickness of 1 μm and a layer of high EW perfluorosulfonic acid resin film layer 3 with a thickness of 1 μm are sequentially coated, and the preparation of the alternating layers is completed;
[0111] The surface of the high EW perfluorosulfonic acid resin film layer 3 is coated with the BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ The low EW perfluorosulfonic acid resin slurry is coated to obtain a composite inner layer 4, and the film thickness is 1 μm;
[0112] The low EW perfluorosulfonic acid resin slurry containing nano-platinum metal prepared in step S4 is coated on the surface of the composite inner layer 4, that is, the composite outer layer 5 is obtained by coating, and the film thickness is 1 μm;
[0113] After the composite inner layer 4 is dried, the composite membrane layer is turned over, and the above coating steps are repeated on the other side of the intermediate membrane layer 1, and the membrane layers with the same structure are symmetrically coated with the intermediate membrane layer 1 as the center, thus completing the preparation of the multilayer proton exchange membrane;
[0114] S8: preparing a membrane electrode for a proton exchange membrane fuel cell, symmetrically coating the catalyst layer slurry prepared in S5 on both sides of the multilayer proton exchange membrane, thereby coating the two side surfaces of the multilayer proton exchange membrane to obtain a catalyst layer 6, the thickness of the catalyst layer 6 on each side is 10 μm, and a functional structure is formed after the coating is completed;
[0115] The edges of both sides of the functional structure are dotted with a 15% solid content perfluorosulfonic acid resin solution, and the 5.5*5.5 cm 2 The low graphitized carbon layer 7 and the medium graphitized carbon fiber layer 8 are formed, the thickness of the low graphitized carbon layer 7 is 10 μm, and the thickness of the medium graphitized carbon fiber layer 8 is 300 μm, thus completing the bonding of the diffusion layer. After the diffusion layer is bonded, the membrane electrode for the proton exchange membrane fuel cell is obtained.
[0116] Comparative Example 1
[0117] The membrane electrode for the proton exchange membrane fuel cell provided in this embodiment is manufactured by the following steps:
[0118] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and isopropanol with an ion exchange equivalent of 600 g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and isopropanol in a volume ratio of 25%:5%:70% to obtain a low EW perfluorosulfonic acid resin composite 5% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0119] S2: preparing a perfluorosulfonic acid resin and n-propanol and directly stirring and mixing them, with a solid content of 25%, to obtain a perfluorosulfonic acid resin slurry;
[0120] S3: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a highly graphitized carbon-based platinum-carbon catalyst obtained at a carbon-based treatment temperature of 2800° C., and isopropanol; firstly wetting the highly graphitized carbon-based platinum-carbon catalyst, and then directly stirring and mixing the wetted highly graphitized carbon-based platinum-carbon catalyst, the perfluorosulfonic acid resin, and the isopropanol in a volume ratio of 2%:7%:91% to obtain a catalytic layer slurry;
[0121] S4: preparing a diffusion layer, using a carbon treatment temperature of 1980° C. to obtain a medium graphitized carbon fiber layer 8, and performing a hydrophobic treatment on the medium graphitized carbon fiber layer 8; and then using a carbon treatment temperature of 1750° C. to obtain a low graphitized carbon layer 7;
[0122] S5: Prepare a multilayer proton exchange membrane by screen printing the intermediate membrane slurry prepared in step S1 into a 6*6 cm 2 The low EW perfluorosulfonic acid resin is compounded with a 5% PVDF film layer, and the film layer thickness is 4 μm, that is, a 4 μm intermediate film layer 1 is prepared;
[0123] After the intermediate film layer 1 is dried, the perfluorosulfonic acid resin slurry prepared in step S2 is coated on one side of the intermediate film layer 1, with a coating thickness of 1 μm;
[0124] After drying, the composite membrane layer is turned over, and the above coating steps are repeated on the other side of the intermediate membrane layer 1, and the membrane layers with the same structure are symmetrically coated with the intermediate membrane layer 1 as the center, thus completing the preparation of the multilayer proton exchange membrane;
[0125] S6: preparing a membrane electrode for a proton exchange membrane fuel cell, symmetrically coating the catalyst layer slurry prepared in S3 on both sides of the multilayer proton exchange membrane, thereby coating the two sides of the multilayer proton exchange membrane to obtain a catalyst layer 6, the thickness of each catalyst layer 6 is 10 μm, and a functional structure is formed after the coating is completed;
[0126] The edges of both sides of the functional structure are dotted with a 15% solid content perfluorosulfonic acid resin solution, and the 5.5*5.5 cm 2 The low graphitized carbon layer 7 and the medium graphitized carbon fiber layer 8 are formed, the thickness of the low graphitized carbon layer 7 is 10 μm, and the thickness of the medium graphitized carbon fiber layer 8 is 300 μm, thus completing the bonding of the diffusion layer. After the diffusion layer is bonded, the membrane electrode for the proton exchange membrane fuel cell is obtained.
[0127] Comparative Example 2
[0128] The membrane electrode for the proton exchange membrane fuel cell provided in this embodiment is manufactured by the following steps:
[0129] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and isopropanol with an ion exchange equivalent of 600 g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and isopropanol in a volume ratio of 25%:5%:70% to obtain a low EW perfluorosulfonic acid resin composite 5% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0130] S2: preparing alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 25%, to obtain a low EW perfluorosulfonic acid resin slurry; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1200 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 25%, to obtain a high EW perfluorosulfonic acid resin slurry;
[0131] S3: preparing a composite inner layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, CeO2 and ethylene glycol, and directly stirring and mixing the perfluorosulfonic acid resin, CeO2 and ethylene glycol in a volume ratio of 25%:5%:70% to obtain a low EW perfluorosulfonic acid resin slurry containing CeO2, i.e., a composite inner layer slurry;
[0132] S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a nano-platinum metal with a particle size of 20 nm-50 nm, and ethanol, and directly stirring and mixing the perfluorosulfonic acid resin, the nano-platinum metal, and the ethanol in a volume ratio of 33%:2%:65% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry;
[0133] S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a highly graphitized carbon-based platinum-carbon catalyst obtained at a carbon-based treatment temperature of 2000° C., and isopropanol; firstly wetting the highly graphitized carbon-based platinum-carbon catalyst, and then directly stirring and mixing the wetted highly graphitized carbon-based platinum-carbon catalyst, the perfluorosulfonic acid resin, and the isopropanol in a volume ratio of 2%:7%:91% to obtain a catalytic layer slurry;
[0134] S6: preparing a diffusion layer, using a carbon treatment temperature of 2000° C. to obtain a medium graphitized carbon fiber layer 8, and performing a hydrophobic treatment on the medium graphitized carbon fiber layer 8; then using a carbon treatment temperature of 1800° C. to obtain a low graphitized carbon layer 7, and performing a hydrophobic treatment on the low graphitized carbon layer 7;
[0135] S7: Prepare a multilayer proton exchange membrane by coating the intermediate membrane slurry prepared in step S1 into a 6*6 cm 2 The low EW perfluorosulfonic acid resin is compounded with a 5% PVDF film layer, and the film layer thickness is 4 μm, that is, a 4 μm intermediate film layer 1 is prepared;
[0136] After the intermediate film layer 1 is dried, the low EW perfluorosulfonic acid resin slurry prepared in step S2 is first coated on one side of the intermediate film layer 1, that is, a low EW perfluorosulfonic acid resin film layer 2 is obtained by coating, and the film layer thickness is 1 μm. After drying, the high EW perfluorosulfonic acid resin slurry prepared in step S2 is then coated, that is, a high EW perfluorosulfonic acid resin film layer 3 is obtained by coating, and the film layer thickness is 1 μm. Then, a layer of low EW perfluorosulfonic acid resin film layer 2 with a thickness of 1 μm and a layer of high EW perfluorosulfonic acid resin film layer 3 with a thickness of 1 μm are sequentially coated, and the preparation of the alternating layers is completed;
[0137] The low EW perfluorosulfonic acid resin slurry containing CeO2 prepared in step S3 is coated on the surface of the high EW perfluorosulfonic acid resin film layer 3, that is, the composite inner layer 4 is obtained by coating, and the film thickness is 1 μm;
[0138] The low EW perfluorosulfonic acid resin slurry containing nano-platinum metal prepared in step S4 is coated on the surface of the composite inner layer 4, that is, the composite outer layer 5 is obtained by coating, and the film thickness is 1 μm;
[0139] After the composite inner layer 4 is dried, the composite membrane layer is turned over, and the above coating steps are repeated on the other side of the intermediate membrane layer 1, and the membrane layers with the same structure are symmetrically coated with the intermediate membrane layer 1 as the center, thus completing the preparation of the multilayer proton exchange membrane;
[0140] S8: preparing a membrane electrode for a proton exchange membrane fuel cell, symmetrically coating the catalyst layer slurry prepared in S5 on both sides of the multilayer proton exchange membrane, thereby coating the two side surfaces of the multilayer proton exchange membrane to obtain a catalyst layer 6, the thickness of the catalyst layer 6 on each side is 10 μm, and a functional structure is formed after the coating is completed;
[0141] The edges of both sides of the functional structure are dotted with a 15% solid content perfluorosulfonic acid resin solution, and the 5.5*5.5 cm 2 The low graphitized carbon layer 7 and the medium graphitized carbon fiber layer 8 are formed, the thickness of the low graphitized carbon layer 7 is 10 μm, and the thickness of the medium graphitized carbon fiber layer 8 is 300 μm, thus completing the bonding of the diffusion layer. After the diffusion layer is bonded, the membrane electrode for the proton exchange membrane fuel cell is obtained.
[0142] Comparative Example 3
[0143] The membrane electrode for the proton exchange membrane fuel cell provided in this embodiment is manufactured by the following steps:
[0144] S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and isopropanol with an ion exchange equivalent of 600 g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and isopropanol in a volume ratio of 25%:5%:70% to obtain a low EW perfluorosulfonic acid resin composite 5% PVDF slurry, i.e., an intermediate membrane layer slurry;
[0145] S2: preparing alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 25%, to obtain a low EW perfluorosulfonic acid resin slurry; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1000 g / mol and directly stirring and mixing it with n-propanol, with a solid content of 25%, to obtain a high EW perfluorosulfonic acid resin slurry;
[0146] S3: Prepare the composite inner layer slurry, select perfluorosulfonic acid resin with an ion exchange equivalent of 600g / mol, BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ and ethylene glycol, perfluorosulfonic acid resin, BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σand ethylene glycol in a volume ratio of 25%:5%:70% and stirred to obtain a mixture containing BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ Low EW perfluorosulfonic acid resin slurry, i.e. composite inner layer slurry;
[0147] S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a nano-platinum metal with a particle size of 20 nm-50 nm, and ethanol, and directly stirring and mixing the perfluorosulfonic acid resin, the nano-platinum metal, and the ethanol in a volume ratio of 33%:2%:65% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry;
[0148] S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600 g / mol, a graphitized carbon-based platinum-carbon catalyst obtained by a carbon-based treatment temperature of 1800° C., and isopropanol; firstly wetting the graphitized carbon-based platinum-carbon catalyst, and then directly stirring and mixing the wetted highly graphitized carbon-based platinum-carbon catalyst, the perfluorosulfonic acid resin, and the isopropanol in a volume ratio of 2%:7%:91% to obtain a catalytic layer slurry;
[0149] S6: preparing a diffusion layer, obtaining a graphitized carbon fiber layer by using a carbon treatment temperature of 1800° C., and performing a hydrophobic treatment on the graphitized carbon fiber layer; obtaining a graphitized carbon layer by using a carbon treatment temperature of 1800° C., and performing a hydrophobic treatment on the graphitized carbon layer;
[0150] S7: Prepare a multilayer proton exchange membrane by screen printing the intermediate membrane slurry prepared in step S1 into a 6*6 cm 2 The low EW perfluorosulfonic acid resin is compounded with a 5% PVDF film layer, and the film layer thickness is 4 μm, that is, a 4 μm intermediate film layer 1 is prepared;
[0151] After the intermediate film layer 1 is dried, the low EW perfluorosulfonic acid resin slurry prepared in step S2 is first coated on one side of the intermediate film layer 1, that is, a low EW perfluorosulfonic acid resin film layer 2 is obtained by coating, and the film layer thickness is 1 μm. After drying, the high EW perfluorosulfonic acid resin slurry prepared in step S2 is then coated, that is, a high EW perfluorosulfonic acid resin film layer 3 is obtained by coating, and the film layer thickness is 1 μm. Then, a layer of low EW perfluorosulfonic acid resin film layer 2 with a thickness of 1 μm and a layer of high EW perfluorosulfonic acid resin film layer 3 with a thickness of 1 μm are sequentially coated, and the preparation of the alternating layers is completed;
[0152] The surface of the high EW perfluorosulfonic acid resin film layer 3 is coated with the BaCe 0.7 Zr0 .1 Y 0.1 Yb0.1 O 3-σ The low EW perfluorosulfonic acid resin slurry is coated to obtain a composite inner layer 4, and the film thickness is 1 μm;
[0153] The low EW perfluorosulfonic acid resin slurry containing nano-platinum metal prepared in step S4 is coated on the surface of the composite inner layer 4, that is, the composite outer layer 5 is obtained by coating, and the film thickness is 1 μm;
[0154] After the composite inner layer 4 is dried, the composite membrane layer is turned over, and the above coating steps are repeated on the other side of the intermediate membrane layer 1, and the membrane layers with the same structure are symmetrically coated with the intermediate membrane layer 1 as the center, thus completing the preparation of the multilayer proton exchange membrane;
[0155] S8: preparing a membrane electrode for a proton exchange membrane fuel cell, symmetrically coating the catalyst layer slurry prepared in S5 on both sides of the multilayer proton exchange membrane, thereby coating the two side surfaces of the multilayer proton exchange membrane to obtain a catalyst layer 6, the thickness of the catalyst layer 6 on each side is 10 μm, and a functional structure is formed after the coating is completed;
[0156] The edges of both sides of the functional structure are dotted with a 15% solid content perfluorosulfonic acid resin solution, and the 5.5*5.5 cm 2 The graphitized carbon layer and the graphitized carbon fiber layer are formed, the thickness of the graphitized carbon layer is 10 μm, and the thickness of the graphitized carbon fiber layer is 300 μm, thus completing the bonding of the diffusion layer. After the diffusion layer is bonded, the membrane electrode for the proton exchange membrane fuel cell is obtained.
[0157] Test Example 1
[0158] The membrane electrodes for proton exchange membrane fuel cells prepared in Examples 1-5 and Comparative Examples 1-2 were prepared into a stack of 30 pieces, and activation and durability tests were performed;
[0159] Activation conditions: hydrogen 0.1MPa (anode), air 0.1MPa (cathode), flow rate 700mL / min, 2800mL / min, 100% humidification, 50℃, 4A, 30min constant current discharge every 2A, 10A, 30min constant current discharge every 5A, 19A, 30min constant current discharge every 2A;
[0160] Endurance test (constant current discharge) conditions: hydrogen 0.1MPa (anode), air 0.1MPa (cathode), flow rate of 700mL / min, 2800mL / min, both 100% humidification, 50℃, 15A constant current discharge for 100h, and continuous recording of stack power and temperature.
[0161] The membrane electrode in the scheme of the present invention increases the mechanical strength of the proton exchange membrane by adding PVDF to the perfluorosulfonic acid resin, thereby increasing durability during repeated swelling. The conductivity of the proton exchange membrane can be increased by using a low EW value resin, and a high EW value resin has higher strength. The mixed resins overlap and interweave to form a network structure, which is beneficial to mass transfer in high-electricity density areas and thus significantly improves fuel cell performance. Preparing a film layer containing rare metal oxides, their doped oxides, and nano-platinum metals on the surface of the proton exchange membrane is beneficial to eliminating free radical corrosion of the proton exchange membrane. The membrane electrode structure designed by the technical scheme of the present invention has a lower ohmic impedance and thus has a higher electron transmission capacity; such as Figure 2 As shown, during the endurance test, the membrane electrode designed by the technical solution of the present invention has a higher overall reaction efficiency and power density, and during the long-term discharge process, the power performance is more stable without obvious attenuation.
[0162] Test Example 2
[0163] The membrane electrodes for proton exchange membrane fuel cells prepared in Example 5 and Comparative Example 3 were prepared into single cells, and activation and reverse polarity tolerance performance tests were performed.
[0164] (1) Activation conditions: hydrogen 0.1 MPa (anode), air 0.1 MPa (cathode), flow rate 700 mL / min, 2800 mL / min, 100% humidification, 50 °C, 4A, 30 min of constant current discharge per 2A, 10A, 30 min of constant current discharge per 5A, 19A, 30 min of constant current discharge per 2A;
[0165] (2) Electrochemically active area (ECSA) test before anode reversal: The single cell was connected to an electrochemical workstation, the anode gas was switched to nitrogen, and the cathode gas was switched to hydrogen after purging. Cyclic voltammetry scanning tests were performed under 100% humidification conditions at a flow rate of 700 mL / min and 2800 mL / min at 0.1 MPa nitrogen (anode), 0.1 MPa hydrogen, with a voltage range of 0.05-1 V and a scan rate of 50 mV / s.
[0166] (3) Reverse polarity tolerance test: The single cell was connected to a DC power supply and the battery was charged at 200 mA cm under the conditions of 0.1 MPa hydrogen (anode), 0.1 MPa air (cathode), flow rates of 700 mL / min and 2800 mL / min, and 60% humidification. -2 The current density is kept stable for a period of time. Then, the anode hydrogen is switched to nitrogen with the flow rate unchanged, and the load is cut off when the voltage drops to the protection voltage of -1.5V.
[0167] (4) Electrochemically active area (ECSA) test after anode reversal: The single cell was connected to an electrochemical workstation, the anode gas was switched to nitrogen, and the cathode gas was switched to hydrogen after purging. Cyclic voltammetry scan tests were performed under 100% humidification conditions at a flow rate of 700 mL / min and 2800 mL / min at nitrogen 0.1 MPa (anode), hydrogen 0.1 MPa, with a voltage range of 0.05-1 V and a scan rate of 50 mV / s.
[0168] like Figure 3 , Figure 4 As shown, through the reverse polarity tolerance test, the electrochemical active area (ECSA) of the membrane electrode before and after the reverse polarity is calculated. It can be seen that the membrane electrode structure design with different graphitization degrees corresponding to Example 5 has no ECSA reduction after the reverse polarity test, indicating that the carbon carrier in the catalyst has not been corroded during the reverse polarity process, so that platinum has not been dissolved, proving that the use of sacrificial other low-graphitization carbon materials can greatly guarantee the electrocatalytic activity of the membrane electrode. Comparative Example 3 uses commercial carbon materials, and the graphitization temperature is 1800°C. According to the reverse polarity tolerance test results, after the reverse polarity test, the ECSA of the membrane electrode is reduced by 6.7%, indicating that the carbon carrier of the catalyst has undergone carbon corrosion during the reverse polarity process, causing the dissolution of platinum particles, thereby significantly reducing the catalytic activity.
[0169] The above description is only a preferred implementation manner of the present invention, but the protection scope of the present invention is not limited thereto, and any modification and replacement based on the technical solution and inventive concept provided by the present invention should be included in the protection scope of the present invention.
Claims
1. A membrane electrode for a proton exchange membrane fuel cell, characterized in that: It includes a multi-layer proton exchange membrane and a catalytic layer and a diffusion layer which are symmetrically arranged on both sides of the multi-layer proton exchange membrane from inside to outside; The multilayer proton exchange membrane comprises an intermediate membrane layer formed by a composite of a low-EW perfluorosulfonic acid resin and PVDF, and alternating layers, a composite inner layer and a composite outer layer symmetrically arranged on both sides of the intermediate membrane layer from the inside to the outside; The alternating layers are alternately composed of at least two low EW perfluorosulfonic acid resin film layers and at least two high EW perfluorosulfonic acid resin film layers; The composite inner layer is a mixture of low EW perfluorosulfonic acid resin and rare metal oxides and dopants thereof; The composite outer layer is a mixture of low EW perfluorosulfonic acid resin and nano-platinum metal; The catalytic layer is a mixture of a low-EW perfluorosulfonic acid resin and a highly graphitized carbon-based platinum-carbon catalyst; The diffusion layer comprises a low-graphitized carbon layer and a medium-graphitized carbon fiber layer arranged from the inside to the outside, and the low-graphitized carbon layer and the medium-graphitized carbon fiber layer are both treated with hydrophobicity.
2. A membrane electrode for a proton exchange membrane fuel cell according to claim 1, characterized in that: The ion exchange equivalent of the low EW perfluorosulfonic acid resin and the low EW fluorosulfonic acid resin membrane layer is 600 g / mol-1000 g / mol, and lower than 1000 g / mol; the ion exchange equivalent of the high EW perfluorosulfonic acid resin and the high EW fluorosulfonic acid resin membrane layer is 1000 g / mol-1200 g / mol.
3. The membrane electrode for a proton exchange membrane fuel cell according to claim 2, characterized in that: The rare metal oxides and dopants thereof in the composite inner layer include CeO2, Ce 0.8 G 0.2 O 1.9 ,BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ 、BaZr 0.8 Yb 0.2 O 3-σ One or more of .
4. The membrane electrode for a proton exchange membrane fuel cell according to claim 3, characterized in that: The high-graphitization carbon-based platinum-carbon catalyst adopts a carbon-based treatment temperature of 2000°C-3000°C to achieve a high degree of graphitization; the medium-graphitization carbon fiber layer adopts a carbon treatment temperature of 1800°C-2000°C, and below 2000°C to achieve a medium degree of graphitization; the low-graphitization carbon layer adopts a carbon treatment temperature of 1400°C-1800°C, and below 1800°C to achieve a low degree of graphitization.
5. A membrane electrode for a proton exchange membrane fuel cell according to any one of claims 1 to 4, characterized in that: The thickness of the intermediate membrane layer is 3-5 μm; the thickness of the low EW perfluorosulfonic acid resin membrane layer is 1-2 μm; the thickness of the high EW perfluorosulfonic acid resin membrane layer is 1-2 μm; the thickness of the composite inner layer is 1-2 μm; the thickness of the composite outer layer is 1-2 μm; the thickness of the multilayer proton exchange membrane is 10-30 μm; the thickness of the catalytic layer is 10-15 μm; the thickness of the low graphitized carbon layer in the diffusion layer is 10-15 μm, and the thickness of the medium graphitized carbon fiber layer is 150-500 μm.
6. A method for preparing a membrane electrode for a proton exchange membrane fuel cell, characterized in that: The following steps are involved: S1: preparing an intermediate membrane layer slurry, selecting a perfluorosulfonic acid resin, PVDF and a high dielectric small molecule alcohol with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, PVDF and the high dielectric small molecule alcohol in a volume ratio of 20%-30%: 5%-10%: 60%-75% to obtain a low EW perfluorosulfonic acid resin composite 5%-10% PVDF slurry, i.e., an intermediate membrane layer slurry; S2: preparing an alternating layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol and directly stirring and mixing it with a high dielectric small molecule alcohol to obtain a low EW perfluorosulfonic acid resin slurry with a solid content of 20%-30%; then selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 1000g / mol-1200g / mol and directly stirring and mixing it with a high dielectric small molecule alcohol to obtain a high EW perfluorosulfonic acid resin slurry with a solid content of 20%-30%; S3: preparing a composite inner layer slurry, selecting a perfluorosulfonic acid resin, a rare metal oxide and a dopant thereof, and a high dielectric small molecule alcohol with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, the rare metal oxide and a dopant thereof, and the high dielectric small molecule alcohol in a volume ratio of 20%-30%: 5%-10%: 60%-75% to obtain a low EW perfluorosulfonic acid resin slurry containing a rare metal oxide and a dopant thereof, i.e., a composite inner layer slurry; S4: preparing a composite outer layer slurry, selecting a perfluorosulfonic acid resin, nano-platinum metal and a high dielectric small molecule alcohol with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol, and directly stirring and mixing the perfluorosulfonic acid resin, nano-platinum metal and high dielectric small molecule alcohol in a volume ratio of 20%-30%: 5%-10%: 60%-75% to obtain a low EW perfluorosulfonic acid resin slurry containing nano-platinum metal, i.e., a composite outer layer slurry; S5: preparing a catalytic layer slurry, selecting a perfluorosulfonic acid resin with an ion exchange equivalent of 600g / mol-1000g / mol and less than 1000g / mol, using a highly graphitized carbon-based platinum-carbon catalyst and a high dielectric small molecule alcohol obtained by a carbon-based treatment temperature of 2000°C-3000°C, and directly stirring and mixing the perfluorosulfonic acid resin, the highly graphitized carbon-based platinum-carbon catalyst and the high dielectric small molecule alcohol in a volume ratio of 2%-5%: 0.8%-4%: 91%-97.2% to obtain a catalytic layer slurry; S6: preparing a diffusion layer, using a carbon treatment temperature of 1800°C-2000°C but lower than 2000°C to obtain a medium-graphitized carbon fiber layer, and performing a hydrophobic treatment on the medium-graphitized carbon fiber layer; and then using a carbon treatment temperature of 1400°C-1800°C but lower than 1800°C to obtain a low-graphitized carbon layer; S7: preparing a multilayer proton exchange membrane, preparing an intermediate membrane layer by using an intermediate membrane layer slurry, and after drying, alternately preparing at least two layers of low-EW perfluorosulfonic acid resin membrane layers and high-EW perfluorosulfonic acid resin membrane layers on the surface of the intermediate membrane layer by using a low-EW perfluorosulfonic acid resin slurry and a high-EW perfluorosulfonic acid resin slurry, drying after each preparation, preparing a composite inner layer by using a composite inner layer slurry on the surface of the top high-EW perfluorosulfonic acid resin membrane layer, and preparing a composite outer layer by using a composite outer layer slurry on the surface of the composite inner layer after drying, and after drying, turning the intermediate membrane layer over and repeating the above steps, symmetrically preparing membrane layers with the same structure to obtain a multilayer proton exchange membrane; S8: Prepare a membrane electrode for a proton exchange membrane fuel cell, prepare a catalytic layer on both sides of the multilayer proton exchange membrane using a catalytic layer slurry, apply a perfluorosulfonic acid resin solution on the edge of the catalytic layer surface after drying, and bond the low-graphitization carbon layer and the medium-graphitization carbon fiber layer prepared in S6 to obtain a membrane electrode for a proton exchange membrane fuel cell after bonding.
7. The method for preparing a membrane electrode for a proton exchange membrane fuel cell according to claim 6, characterized in that: The rare metal oxides and dopants thereof in step S3 include CeO2, Ce 0.8 G 0.2 O 1.9 ,BaCe 0.7 Zr0 .1 Y 0.1 Yb 0.1 O 3-σ 、BaZr 0.8 Yb 0.2 O 3-σ One or more of .
8. The method for preparing a membrane electrode for a proton exchange membrane fuel cell according to claim 6 or 7, characterized in that: The high dielectric small molecule alcohol includes one or more of ethanol, ethylene glycol, n-propanol, and isopropanol.
9. The method for preparing a membrane electrode for a proton exchange membrane fuel cell according to claim 6, characterized in that: The intermediate film layer, the low EW perfluorosulfonic acid resin film layer, the high EW perfluorosulfonic acid resin film layer, the composite inner layer, the composite outer layer and the catalytic layer are all prepared by coating or screen printing.